Clinical profile and associated comorbidities of cerebral palsy in children visiting Orotta National Referral Hospital, Eritrea: a cross-sectional study - Yohannes Kibrom; Emnet Tekeste; Sirak Tesfamariam; Zemichael Ogbe; Mahmud Mohammed (BMC, 2024)
Abstract Background Cerebral Palsy (CP) is one of the most common physical disabilities in children. This study aimed to explore the clinical spectrum of CP at Orotta National Referral and Teaching Hospital, including CP subtypes, gross motor function, patterns of associated comorbidities, and possible risk factors in children aged 2 to 12 years. Methods A hospital-based cross-sectional study was conducted from January to April 2022 in 153 children with suspected motor symptoms. The Surveillance of CP in Europe (SCPE) decision tree was used as an inclusion criteria guideline and the evaluation of the participants was done using a standardized questionnaire and clinical examination. Descriptive statistics, chi-square test, and logistic regression were employed to statistically analyze the data. Results Eighty-four children who fulfilled the clinical criteria were included in the study. The median age was 5-years [IQR: 3.8] with an equal distribution of males and females. Quadriplegic CP was the most common subtype (51.2%) followed by unilateral (hemiplegic) CP (22.6%), and dyskinetic CP (14.3%). Most children had severe gross motor impairment GMFCS level IV-V and females were almost three times more likely to have GMFCS level IV/V than males (AOR: 2.70; CI: 1.08-6.72; p-value = 0.033.) More than half (52.4%) of the neonates either did not cry within five minutes and/or needed breathing resuscitation, 55.3% had to be admitted to the NICU with a median of 5 days' hospital stay. Between the first week of birth and the first year of life, 28.6% had trouble feeding, 26.2% had an infection, 10.7% had difficulty breathing, 20.2% had seizures and 6% had jaundice. Feeding problems (64.3%), speech problems of some sort (91.7%), and epilepsy (46.4%) were the most commonly associated comorbidities with CP. Conclusions The clinical profile of the CP patients was found to be dominated by the spastic subtype and moderate to severe disability. Since perinatal risk factors were found to be dominant, strengthening maternal and child healthcare systems is recommended to minimize incidents of preventable risk factors and the burden of the disability.